PENGARUH ANALISIS JABATAN, STRUKTUR ORGANISASI DAN KOMPETENSI TERHADAP KINERJA PEGAWAI PADA BADAN PERENCANAAN PENELITIAN DAN PEMBANGUNAN DAERAH (BAPPEDA) KABUPATEN MOROWALI - Yurniati, Yurniati (Katalogis, 2016)
The objectives of this research are: 1) to determine and analyze simultaneous influence of job analysis, organizational structure, and competency on civil servants performance in The Agency of Planning, Research, and Regional Development of Morowali Regency; 2) to determine and analyze the influence of job analysis on civil servants performance; 3) to determine and analyze the influence of organizational structure on civil servants performance; 4) to determine and analyze the influence of competency on civil servants performance. The type of the study is explanatory to show relationships of variables studied by involving 40 respondents who are selected through purposive sampling technique. The result of multiple linear regressions test shows that 1) job analysis, organizational structure, and competency simultaneously have positive and significant influence on employees performance in The Agency of Planning, Research, and Regional Development of Morowali; 2) job analysis positively and significantly influences the performance of employees; 3) organizational structure positively and significantly influences the performance of employees; 4) competency positively and significantly influences the performance of employees.